2020
DOI: 10.1556/2050.2018.00008
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress effects on appetite: Changing desire for high- and low-energy foods depends on the nature of the perceived threat

Abstract: It is well-documented that harsh environmental conditions influence appetite and food choice. However, the experience of environmental harshness is complex and shaped by several underlying dimensions, notably threats to one's social support, economic prospects, and physical safety. Here, we examined the differential effects of these three dimensions of environmental harshness on desire for specific food items. We first showed 564 participants images of 30 food items. Next, they rated how much they desired each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…26,27 Swaffield B Jim & Guo Qi said that the anxiety and stress in young women would affect their appetite that will certainly impact their nutritional status. 28 It is different from the results of research conducted by Kurniawati Widi & Luh Made K.S who argue that anxiety and stress will increase the appetite. 27 Malnutrition in adolescent would affect of the reproductive organ function.…”
Section: Introductionmentioning
confidence: 72%
“…26,27 Swaffield B Jim & Guo Qi said that the anxiety and stress in young women would affect their appetite that will certainly impact their nutritional status. 28 It is different from the results of research conducted by Kurniawati Widi & Luh Made K.S who argue that anxiety and stress will increase the appetite. 27 Malnutrition in adolescent would affect of the reproductive organ function.…”
Section: Introductionmentioning
confidence: 72%
“…One possible reason is that different types of environmental stressors have different effects on appetite. As noted by [ 14 ], financial stress tends to increase appetite whereas concerns about physical safety tend to decrease appetite.…”
Section: Discussionmentioning
confidence: 99%
“…The specific food items can be found in Table 1 . For further details on the images used in this study, please refer to Swaffield and Gou [ 14 ]. With regards to the food items selected to be included in each of the six food categories, there were no inclusion requirements other than to ensure variety.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress of COVID-19 and the quarantine increased depression, anxiety and other mental health issues [25,26]. Stress can cause changing in appetite, energy, desires, and interests [27]. Studies reported an increased restriction in COVID-19 patients with anorexia nervosa [28,29].…”
Section: Discussionmentioning
confidence: 99%